2016
DOI: 10.1177/1078155215625459
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of granulocyte colony-stimulating factors to prevent febrile neutropenia and related complications in cancer patients in clinical practice: A systematic review

Abstract: Based on the findings from this review of real-world comparative effectiveness studies, risks of FN and FN-related complications were generally lower for prophylaxis with pegfilgrastim versus prophylaxis with short-acting G-CSFs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 44 publications
0
48
0
2
Order By: Relevance
“…Presently, there are two G-CSF types available on the market: the short-acting G-CSF, including filgrastim, tbo-filgrastim, filgrastim-sndz and lenograstim, and the pegylated long-acting one (pegfilgrastim and lipegfilgrastim). Pegfilgrastim was the first approved long-acting G-CSF product [10][11][12] • patient age > 65…”
Section: Colony Stimulating Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Presently, there are two G-CSF types available on the market: the short-acting G-CSF, including filgrastim, tbo-filgrastim, filgrastim-sndz and lenograstim, and the pegylated long-acting one (pegfilgrastim and lipegfilgrastim). Pegfilgrastim was the first approved long-acting G-CSF product [10][11][12] • patient age > 65…”
Section: Colony Stimulating Factorsmentioning
confidence: 99%
“…However, studies comparing the efficacy of long-and short-acting G-CSF products indicate that a lower efficacy of the latter is often associated with an insufficient duration of their administration, i.e. from 3 to 7 days[12,19].g-csF ImPAct ON tHE EFFIcAcy OF cHEmOtHErAPyit has been demonstrated that G-CSF reduces the risk of febrile neutropenia, mortality related to infections, and the number of premature deaths[9,21].Dose-reducing toxicity, including myelotoxicity, is one of the chief factors impacting the efficacy of anti-cancer treatment[1][2][3][4]. intensified and prolonged neutropenia results in dose reduction and delayed administration of the consecutive cycles of chemotherapy, which in turn reduces its efficacy.…”
mentioning
confidence: 99%
“…On recovery, subsequent chemotherapy doses could be reduced; however, this would diminish their efficacy when given with curative intent. The advent of the use of granulocyte colony‐stimulating factor, longer‐acting formulations and recombinant stem cell factor, given with chemotherapy, has significantly decreased the severity and duration of neutropenia, thereby reducing the chance of infection or hastening recovery 1 . With this strategy, the dose intensity of chemotherapy can be maintained.…”
Section: Broadening the Spectrum Of Treatable Side Effectsmentioning
confidence: 99%
“…G-cSF can act as a mobilizer of hematopoietic progenitor stem cells in blood donors or cancer patients (10). Therefore, recombinant human G-cSF (rhG-cSF) is commonly used to prevent and treat febrile neutropenia and mucositis after chemotherapy and radiotherapy for cancer patients (11). However, recent studies have found that G-cSF plays a crucial role in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%